2019
DOI: 10.1186/s42269-019-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicobacteriological study of chronic dacryocystitis in Egypt

Abstract: Background: Empirical antibiotic treatment is a common practice to manage chronic dacryocystitis in many healthcare settings in spite of the probability for changing in the types of microbial isolates. The aims of this study were to find out the current clinicomicrobiological profile of adult cases with chronic dacryocystitis and to determine the antibiogram of the isolated organisms to the commonly prescribed antibiotics. Results: Of the 25 samples obtained, 15 (60%) yielded a positive culture, 12 (48%) showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Among all the analyzed P. aeruginosa isolates, the highest resistance was observed to aztreonam. The results of Negm et al's study confirm our results, showing that Gram-negative isolates were more sensitive to the third generation of cephalosporins, such as cefotaxime (80%) and ceftazidime (60%) (2). In the Enterobacteriaceae group, the highest (100%) sensitivity was to amikacin, gentamicin, ciprofloxacin, cefotaxime, piperacillin-tazobactam, and augmentin in Klebsiella.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Among all the analyzed P. aeruginosa isolates, the highest resistance was observed to aztreonam. The results of Negm et al's study confirm our results, showing that Gram-negative isolates were more sensitive to the third generation of cephalosporins, such as cefotaxime (80%) and ceftazidime (60%) (2). In the Enterobacteriaceae group, the highest (100%) sensitivity was to amikacin, gentamicin, ciprofloxacin, cefotaxime, piperacillin-tazobactam, and augmentin in Klebsiella.…”
Section: Discussionsupporting
confidence: 86%
“…In this situation, microorganisms, such as normal flora or pathogens, can be colonized within the lacrimal sac (1). Clinical symptoms of dacryocystitis include pain, redness, and swelling over the inner side of the lower eyelid (2). The microbial agents of this disease have not been described in different geographical areas.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical specimens for bacterial examination were collected from all these 60 (from a total of 67 eyes, as 7 patients had bilateral involvement) clinically diagnosed cases of chronic dacryocystitis after obtaining informed consent. Chronic dacryocystitis patients are the ones with persistent watering of the eyes for longer duration, thickening of the lacrimal drainage system and regurgitation of mucoid and mucopurulent material on pressure over lacrimal sac area or on irrigation of lacrimal drainage system 12 . The patients were asked to wash the face with soap and water, especially around the affected eye, and allowed to air dry.…”
Section: Collection Of Samplementioning
confidence: 99%
“…Insufficient lacrimal drainage leads to the colonization of microorganisms, leading to infection in the lacrimal sac. In previous studies, it has been shown that inflammation and fibrosis occur secondary to bacterial colonization in the lumen of the lacrimal sac in chronic cases [1,5]. Chronic dacryocystitis poses a potential risk of infection to the cornea and other neighboring tissues [6].…”
Section: Introductionmentioning
confidence: 99%